Optical and mechanical optimization of hydrogel for passive cooling - Zhu, Xiyang (Nanyang Technological University, 2022)
As global warming and the energy consumption issue increases, the role of the solar energy industry in sustainable development is becoming more and more important in recent years. One of the most potential solar energy technologies is the PV system, a kind of electric power system that absorbs and converts sunlight into electricity. Driven by technological advances and huge market potential, millions of PV systems have been distributed worldwide, and the number is still growing rapidly. One of the essential issues to be solved in today's solar PV system is excessive heat generation on the surface of the PV panels under sunlight, which greatly reduces the energy efficiency and shortens the lifetime of the PV panel. Therefore, an effective cooling solution is required to improve the solar energy utilization of solar PV systems. In the first half of this report, we simply introduce the principle of the solar power PV system and explain the reason that PV cooling is required, also review the relevant active & passive cooling methods and application used for solar power PV systems, and we subsequently introduce the PVA hydrogel with its development & current application, and different preparation methods. Based on the objective, by carrying out a series of preparation experiments with different compositions, molecular weights and controlling the cross-linking agent, and conducting the light transmittance and mechanical test for each specimen, at the end of this project, we successfully prepared a PVA hydrogel with high light transmittance, high level of water content and excellent mechanical to realize a passive cooling effect on PV panel and improve the solar energy conversion efficiency of PV solar cell, hence providing the low-cost & simple cooling solution for solar power PV systems and promoting the further development on PV solar industry